The combined use of screening and quantum defect parameters in the study of ionized atoms - Aguiar, Julio C. (2015)
The screened hydrogenic model (SHM) is one of the atomic models commonly used in plasma physics, especially in the high energy density range. However, for low-ionization degrees, the radial hydrogenic wavefunctions of the valence electrons are very different from those arising from Hartree Fock (HF) calculations. In this work we used the time-honored concepts of screening and quantum defects to calculate the atomic structure and spectra of not very highly ionized atoms. We showed that, although for neutral and few ionized atoms the screened hydrogenic radial wave functions are far from the HF values, the combined use of the screening and the quantum defect parameters produces better calculations of the dipolar moments that using only the SHM.